2023
DOI: 10.1186/s13034-023-00604-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and costs of singaporean youth with symptoms of depression and anxiety: results from a 2022 web panel

Abstract: Background There is evidence that the prevalence of depression and anxiety among youth is increasing and that these factors contribute to high healthcare costs and poor school performance. The goal of this study is to provide up-to-date estimates of the prevalence and economic burden of depression and anxiety among youth in Singapore. Methods Using an existing web panel, 991 parents filled out the PHQ-4 screener on behalf of 1,515 youth. 104 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…3,4 In a recent study of Singaporean youth, 16.2 percent of youth had symptoms consistent with depression and anxiety. 5 While depression and anxiety are the leading cause of morbidity worldwide for adolescents and young people, other mental health conditions remain prevalent in this age group, including eating disorders, problematic internet usage, bipolar disorder, conduct disorder, and ADHD. 6,7 While causes of mental health conditions are complex and often multifactorial, academic stress, peer relationships, and social media are often unique contributing factors in adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 In a recent study of Singaporean youth, 16.2 percent of youth had symptoms consistent with depression and anxiety. 5 While depression and anxiety are the leading cause of morbidity worldwide for adolescents and young people, other mental health conditions remain prevalent in this age group, including eating disorders, problematic internet usage, bipolar disorder, conduct disorder, and ADHD. 6,7 While causes of mental health conditions are complex and often multifactorial, academic stress, peer relationships, and social media are often unique contributing factors in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 If left untreated, mental health conditions in adolescence are likely to lead to decreased school attendance, worsening school performance, adult mental health disorders, poorer quality of life, higher risk of substance use, and social isolation. 5,10,11 Significantly, these conditions are also associated with increased healthcare costs, both for direct treatment as well as evaluation of possible organic causes or somatic symptoms. In Singapore, these costs are estimated at $1.2 billion per year.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A recent 2022 study in Singapore showed that 11.7 percent of youth displayed symptoms indicative of depression. 2 As is the case for many common medical conditions, family doctors play an essential role in detecting and managing adolescent depression. Identifying the signs, elucidating causal and contributory factors, and implementing appropriate interventions are essential steps in closing the large treatment gap 3 and providing effective care to the generation that will be tomorrow's working adults.…”
Section: Introductionmentioning
confidence: 99%